CRIMINAL VICTIMISATION OF RIDESHARING DRIVERS IN LAGOS STATE (2023)
Globally, criminal victimisation has become a security threat in the ridesharing industry, which uses digital application to connect riders to drivers. In Nigeria, criminal victimisation has become prevalent among drivers working with prominent ridesharing companies in Lagos State. Existing studies described the self-protective behaviours of ridesharing drivers, with scant attention paid to the social context of their victimisation and lived experiences. This study, was therefore designed to investigate the nature of victimisation,factors associated with its occurrence, its risks as well as the preventive measures provided by ridesharing companies to protect drivers in Lagos State. The Routine Activity Theory provided the framework, while the exploratory design was employed.Lagos State was purposively selected due to the recorded prevalence of ridesharing victimisation. Two prominent ridesharing companies were purposively selected because they are the leading players in the ridesharing industry. In all, 45 in-depthinterviews were conducted. This comprised 30 drivers (15 in each of the two companies), 10 riders and five police officers in the Rapid Response Squad who had handled ridesharing victimisation cases. A key informant interview was also conducted with anoperations manager of one of the companies to understand safety and preventive measures put in place for drivers. These were complemented with 10 reported cases of victimisation in the Vanguard and Punch newspapers, selected because of their extensivecoverage on ridesharing victimisation. The data were thematically analysed. The 30 ridesharing drivers were male. Of these, 18 worked on full-time, while 12 worked on part-time basis. Cash-dominated payment system, working late at night and the type of cars used by ridesharing drivers exposed them to victimisation from crime-motivated riders. The drivers experienced violent attacks from crime-motivated riders, resulting in loss of cars, phones and money. They also sustained bodily injuries, while some of their colleagues died in the process. Despite reported victimisation of ridesharing drivers, ridesharing companies were reported to have done little or nothing to secure the lives and valuables of their drivers who had suffered varying degrees of victimisation. Although,ridesharing companies reported that there were security measures put in place, such as the rating system and insurance, the ridesharing drivers noted that these measures were insufficient to protect them from crime-motivated riders. The police statedthat installing security camera in ridesharing cars would be helpful in deterring crime-motivated riders and enhance the safety of drivers. Criminal victimisation of ridesharing drivers manifested in the form of physical injury, loss of lives, and dispossession of valuables. Drivers should avoid crime hot-spots and timing of their operation while ridesharing companies should install tracking devices on their cars.